“They ask me: why consult with a pharmacist?” - Patients’ experiences with a comprehensive medication management service (Research, Society and Development, 2021)
This study aims to reveal the patients’ experiences with a comprehensive medication management (CMM) service delivered in a specialty pharmacy in Brazil. This is a qualitative study performed from September 2015 to February 2016. In-depth semi-structured interviews were conducted with 10 patients followed-up in a CMM service in a specialty pharmacy located in Minas Gerais state. The interviews were recorded, transcribed and analyzed with the assistance of the NVivo11® software. According to the participants, they did not know what to expect from CMM at first. They showed difficulties on establishing a solid concept for CMM, however, they pointed some key aspects of pharmaceutical care philosophy based on their experience with the service. The interviewees identified the CMM pharmacist, seen as a care professional, as a different professional compared to the traditional pharmacist, mainly identified by them as a salesman. The ability to listen and the time that the CMM professional dedicated in the consultations were highlighted as primordial in the process of building a therapeutic relationship with the patient. The difficulties the patients have for establishing a solid concept for CMM might be due to the lack of pharmacists exerting this function, considering CMM is still a new service in Brazil. The results of this work can guide efforts to build a better interaction between patients and pharmacists, in a constant search for offering the best care possible.